O CRM NO CONTEXTO DAS BIBLIOTECAS: PROPOSTA DE IMPLANTAÇÃO NA BIBLIOTECA CENTRAL DO CEFET/RJ - Lima, Lívia da Fraga (2013)
This study approaches the Customer Relationship Management (CRM) on a perspective of strategic management of academic libraries, by submitting a proposal for the implementation of CRM in the Central Library of CEFET/RJ. This research is applied and, in accordance to its goal, it is exploratory, presenting the main theoretical aspects related to Relationship Marketing and CRM. The research method adopted was the case study, with application of a specific instrument to measure the degree of relationship of the library with its clients. The instrument was sent to 2.006 members, of whom 476 participated of the survey. The transposition of the steps involved in the implementation of CRM in the context of companies was done to the studied environment, with the help of a preliminary test-pilot. After collecting and analyzing the data, it was identified that the library in question has a good relationship with its users, however, many aspects can be improved. So, fundamentally this study contributes to the strengthening of theoretical studies in librarianship, facing on the strategic management of libraries and in user studies, serving as an instrument of support for libraries that wish to implement such management.